TASK-BASED LEARNING APPROACH IN ACTION: READING FOR ACADEMIC PURPOSES CLASS (A RESULT OF CLASSROOM ACTION RESEARCH) - Noer Doddy Irmawati Ahmad Dahlan University (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
English achievement of the students of Faculty of Letters Ahmad Dahlan University Yogyakarta is low. The indicator is the English ability of the students, because English has an important role as an International language in the world. Besides the result of learning RAP of the students shows in average scores of 56-65 (C). The problems which are discussed in this research are: 1) the effort of how to improve the achievement of RAP by using TBL and 2) the evidence that shows as the English achievement of the students in studying RAP. TBL, which is used in the treatment is done into 3 cycles: the first cycle has been done by 4 meetings, the second cycle has been done by 4 meetings, and the third cycle has been done by 4 meetings. All the teaching–learning process of RAP is done by collaboration and creativity in preparing materials. It is a result of CAR which is done in Reading Class A Faculty of Letters UAD Yogyakarta from June up to December 2008. There are planning, preventative steps of performance, observation, and reflection. The data are taken from the real condition that the result of learning process of RAP of the students is low. To get the data the researcher does an observation, an interview, besides asking the students to fulfilling the form, giving test, and analyzing document. Data validity investigation technique which is used in this research is Data Resource Triangulation and Method Triangulation. Informant Review is also used in Data Validity Test. Reliability Estimation to guarantee the reliability of Data are found by Test and Observation. To analyze the data the researcher uses the result of observation that is reflected and the learning result of the students that is achievement. The technique of analyzing the data is Descriptive Statistic Technique and Critical Analysis to know the improvement of the situation in detail and precisely according to the improving of the treatment in each cycle that is the improvement of the 1st, the 2nd, and the 3rd cycles. After having the preventative steps of performance by using TBL in RAP which have been done in the first, in the second, and in the third cycles, there is a significant result. It shows that more than 75% of the students who have got good grade with more than 65 scores. There are 20 of 27 students get good scores: 10 students (37,04%) get the score between 66-79 (B); and 12 students (44,44%) get the score between 80-88 (A), and 5 students (18,52%) get C (56-65). It means that there is a significant improvement of English achievement by using TBL in teaching RAP. The Affective Aspect and the Psychomotor Aspect are also significantly increased, because according to the result of Paired Sample Test, the correlation significant shows below 0,05 (